The mobilizing and demobilizing effects of political TV ads: A midterm election study. (August 2018) - Llaudet, Elena
Abstract: Does exposure to political TV ads affect voter turnout? And does the effect depend on whether the ads are positive or negative? Comparing areas that in 2014 were accidentally exposed to intense political advertising to areas that were not, we find that exposure to political commercials stimulates the electorate when the volume of negative ads is equivalent to the volume of positive ads. As the volume of negative ads increases, however, the effect of exposure on turnout significantly decreases and even reverses in sign. This research helps reconcile important debates in the literature, as it is the first aggregate-level study to find evidence consistent with the separate mobilizing and demobilizing effects of political advertising identified in laboratory experiments.